Tell me with what you play and I’ll tell you who you will be. Analysis of Christmas Advertising Campaigns of children’s toys in broadcast television in Lima (2011-2012) - Mendoza Cuéllar, Héctor (2013)
This article presents research describing gender roles offered to boys and girls from Christmas toy advertising through broadcast television in Lima. These messages provide content that lead to the adoption of stereotypical gender roles from an early age, which are perpetuated throughout life. This article has been worked on a multidisciplinary approach and from a quantitative and qualitative perspective. Analysis was performed first toy market in Lima, the number of spots broadcast during the Christmas season, and then select the most emission spots and analyze how gender representations proposed. The different and complementary looks seek to understand this reality and how widespread evidence to bring these campaigns to propose new ways to build more equitable sexuality advertising.